Abstracts Communications Orales –Neuroradiologie - ORL_ JRANF 2025_JAIM 2025_17.3 - ABDITS GG; MOYIKOUA RF; DOUMBOUYA I S; A.W.B. BATCHAM; DIATEWA JE; MATINUNGINA KITUBA AIME; MEDILA MOUSSA ALI; NEOSSI GUENA Mathurin; MOULION TATOUH JEAN ROGER; NGOMA NIANGUI L; et al. (Journal Africain d Imagerie Médicale (J Afr Imag Méd) Journal Officiel de la Société de Radiologie d’Afrique Noire Francophone (SRANF), 2025)
3- Abstracts Communications Orales –Neuroradiologie - ORL_ JRANF 2025_JAIM 2025_17.3